If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + 11) = 5(x + 7) Reorder the terms: 2(11 + 3x) = 5(x + 7) (11 * 2 + 3x * 2) = 5(x + 7) (22 + 6x) = 5(x + 7) Reorder the terms: 22 + 6x = 5(7 + x) 22 + 6x = (7 * 5 + x * 5) 22 + 6x = (35 + 5x) Solving 22 + 6x = 35 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 22 + 6x + -5x = 35 + 5x + -5x Combine like terms: 6x + -5x = 1x 22 + 1x = 35 + 5x + -5x Combine like terms: 5x + -5x = 0 22 + 1x = 35 + 0 22 + 1x = 35 Add '-22' to each side of the equation. 22 + -22 + 1x = 35 + -22 Combine like terms: 22 + -22 = 0 0 + 1x = 35 + -22 1x = 35 + -22 Combine like terms: 35 + -22 = 13 1x = 13 Divide each side by '1'. x = 13 Simplifying x = 13
| 5x+12=-103 | | 3(6x+4)=58 | | 5(9+6x)=105 | | -7y=42 | | 3x+6=8+x | | 2x-15=8x-3 | | 7(8+x)=28 | | -5x+9-x=-45 | | 5(7+7x)=-105 | | -5(-5+6x)=-305 | | 25x^2-20x-3=0 | | r^3-64=0 | | -5(-10+4x)=10 | | 8+3x+2x=43 | | 3(-4x+4)=84 | | 3x+8=5x+18 | | 14x-13=8x-7 | | 7x-4=4x+17 | | -2x+10=-38+4x | | 6+3x=-2x-39 | | 3x+6=7x+2 | | (x+6)1.5=2x | | 3x+1=10-6x | | 10k-4k=12 | | 9+2x=-3x-51 | | -6x-6=-78+6x | | x+25-2x+4=19 | | 5x^2+36x+7=0 | | 9x+6=6x-9 | | -132=12(n+9) | | x^3+7x^2+7x+49=0 | | x^2+8x+14=0 |